2019
DOI: 10.1038/s41398-019-0619-y
|View full text |Cite
|
Sign up to set email alerts
|

Adult attention-deficit/hyperactivity disorder is associated with reduced norepinephrine transporter availability in right attention networks: a (S,S)-O-[11C]methylreboxetine positron emission tomography study

Abstract: The norepinephrine transporter (NET) has been suggested to play a critical role in attention-deficit/hyperactivity disorder (ADHD). In this prospective controlled study we tested the a-priori-hypothesis that central NET availability is altered in adult ADHD patients compared to healthy controls. Study participants underwent single positron emission tomography-magnetic resonance imaging (PET-MRI). MRI sequences included high resolution T1-MPRAGE data for regions of interest (ROI) delineation and voxel-based mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 30 publications
(31 citation statements)
references
References 58 publications
2
29
0
Order By: Relevance
“…Brain imaging studies have shown that dopamine and norepinephrine pathways are involved in the pathology of ADHD. Dopamine and norepinephrine pathways are also involved in other comorbid disorders such as depression, anxiety, and panic (27)(28)(29)(30)(31)(32)(33). Therefore, it is not surprising that by regulating these pathways some improvements occur in mood and concentration of ADHD patients; they also show why MPH is effective for the treatment of ADHD (34).…”
Section: Discussionmentioning
confidence: 99%
“…Brain imaging studies have shown that dopamine and norepinephrine pathways are involved in the pathology of ADHD. Dopamine and norepinephrine pathways are also involved in other comorbid disorders such as depression, anxiety, and panic (27)(28)(29)(30)(31)(32)(33). Therefore, it is not surprising that by regulating these pathways some improvements occur in mood and concentration of ADHD patients; they also show why MPH is effective for the treatment of ADHD (34).…”
Section: Discussionmentioning
confidence: 99%
“…Dopamine and noradrenaline play important roles in high-level executive functions in attention-deficit/hyperactivity disorder (ADHD) by influencing the fronto-striato-cerebellar circuits [ 6 ]. ADHD is associated with reduced noradrenaline (norepinephrine) transporter availability in right attention networks [ 38 ]: noradrenaline (norepinephrine) reuptake inhibitors inhibit the uptake of primarily norepinephrine by presynaptic nerve terminals and increase its availability in the synaptic cleft by blocking the human norepinephrine transporter [ 17 ]. Dopamine influences the attention, concentration and motivation.…”
Section: Discussionmentioning
confidence: 99%
“…This implies that MPH could still affect noradrenergic transmission through DAT inhibition. Moreover, we cannot exclude that some NETrelated FC changes that do not reach statistical significance at rest may emerge during a paradigm preferentially engaging attentional networks [73,74]. Finally, we acquired data on a single time-interval post-dosing with a single low dose.…”
Section: Discussionmentioning
confidence: 99%